An introduction to law and regulation: text and materials - Morgan, Bronwen (Law in context series, 2007)
Theories of regulation -- Regulatory instruments and techniques -- Regulatory enforcement and compliance -- Regulatory accountability and legitimacy -- Regulation above and beyond the state